Understanding the Burden of Tuberculosis among American Indians/Alaska Natives in the U.S.: A Validation Study. (July 2014) - Podewils, Laura Jean; Alexy, Emily; Driver, Stephani Jean; Cheek, James E.; Holman, Robert C.; Haberling, Dana; Brett, Meghan; McCray, Eugene; Redd, John T.
Objective: We validated cases of active tuberculosis (TB) recorded in the Indian Health Service (IHS) National Patient Information Reporting System (NPIRS) and evaluated the completeness of TB case reporting from IHS facilities to state health departments. Methods: We reviewed the medical records of American Indian/Alaska Native (AI/AN) patients at IHS health facilities who were classified as having active TB using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnostic codes from 2006 to 2009 for clinical and laboratory evidence of TB disease. Individuals were reclassified as having active TB disease; recent latent TB infection (LTBI); past positive tuberculin skin test (TST) only; or as having no evidence of TB, LTBI, or a past positive TST. We compared validated active TB cases with corresponding state records to determine if they were reported. Results: The study included 596 patients with active TB as per ICD-9-CM codes. Based on chart review, 111 (18.6%) had active TB; 156 (26.2%) had LTBI; 104 (17.4%) had a past positive TST; and 221 (37.1%) had no evidence of TB disease, LTBI, or a past positive TST. Of the 111 confirmed cases of active TB, 89 (80.2%) resided in participating states; 81 of 89 (91.2%) were verified as reported TB cases. Conclusions: ICD-9-CM codes for active TB disease in the IHS NPIRS do not accurately reflect the burden of TB among AI/ANs. Most confirmed active TB cases in the IHS health system were reported to the state; the national TB surveillance system may accurately represent the burden of TB in the AI/AN population.